Stevia as an alternative crop for tobacco production in RN Macedonia - Dimov Zoran; Iljovski Igor; Canev Ile (Ratarstvo i Povrtarstvo)
The reform of the Common Agricultural Policy (CAP) for the tobacco sector in the European Union aims to gradually phase out subsidies for tobacco cultivation, a change that will significantly impact the tobacco industry in the Republic of North Macedonia. As a response, one proposed adaptation strategy is the cultivation of alternative crops to maintain employment levels and market competitiveness with new products. Stevia (Stevia rebaudiana Bertoni) was explored as a potential alternative crop that local farmers could adopt. Field experiments were conducted in 2019 across three localities (L1 - L3) on seven experimental fields (EF1 - EF7). The results revealed that EF3 achieved the highest yield of dry biomass at 4,400 kg/ha, followed by EF7 and EF1 (3900 kg ha-1 and 3580 kg ha-1 respectively), showing significant differences with other fields (p < 0.05). The highest dry leaf yield (1,400 kg ha⁻¹) was observed at EF7, with statistical differences with EF6, EF5, and EF4. Among the localities, dry biomass yield was significantly higher at L3 (3,250 kg ha⁻¹) and L1 (3,115 kg ha⁻¹), compared with L2 (2,450 kg ha⁻¹). Based on dry leaf L3 producing the highest yield (935 kg ha⁻¹), significantly greater than L1 (840 kg ha⁻¹) and L2 (875 kg ha⁻¹). While some findings, such as the dry biomass yield are promising, the overall results obtain from one year of investigation are insufficient to recommend stevia as a viable alternative crop for the tobacco-growing regions of the country at this time.